Comparative study of Candida spp. isolates: Identification and echinocandin susceptibility in isolates obtained from blood cultures in 15 hospitals in Medellín, Colombia (2018)
Objectives: Invasive candidiasis has a high impact on morbidity and mortality in hospitalised patients. Accurate and timely methods for identification of Candida spp. and determination of echinocandin susceptibility have become a priority for clinical microbiology laboratories. Methods: This study was performed to compare matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF/MS) identification with sequencing of the D1/D2 region of the rRNA gene complex 28 subunit in 147 Candida spp. isolates obtained from patients with candidaemia. Antimicrobial susceptibility testing was performed by broth microdilution (BMD) and Etest. Sequencing of the FKS1 and FKS2 genes was performed. Results: The most common species isolated were Candida albicans (40.8%), followed by Candida parapsilosis (23.1%) and Candida tropicalis (17.0%). Overall agreement between the results of identification by MALDI-TOF/MS and molecular identification was 99.3%. Anidulafungin and caspofungin susceptibility by the BMD method was 98.0% and 88.4%, respectively. Susceptibility to anidulafungin and caspofungin by Etest was 93.9% and 98.6%, respectively. Categorical agreement between Etest and BMD was 91.8% for anidulafungin and 89.8% for caspofungin, with lower agreements in C. parapsilosis for anidulafungin (76.5%) and C. glabrata for caspofungin (40.0%). No mutations related to resistance were found in the FKS genes, although 54 isolates presented synonymous polymorphisms in the hotspots sequenced. Conclusions: MALDI-TOF/MS is a good alternative for routine identification of Candida spp. isolates. DNA sequencing of the FKS genes suggested that the isolates analysed were susceptible to echinocandins; alternatively, unknown resistance mechanisms or limitations related to antifungal susceptibility tests may explain the resistance found in a few isolates. © 2017 International Society for Chemotherapy of Infection and Cancer